Prevention of occupational hazards in the Algerian public institution - Kahoul, Romaissa; Bouhouche, Hichem (Journal of Human Sciences, 2022)
This paper discusses the various aspects of work accidents in the company their negative impacts on workers and on the environment and how to prevent them, through a quick review of the literature on the subject. It also addresses the prevention of accidents and their reduction in the light of the Algerian industrial sector evolution and the labor legislation which accompanied it the most.